Leakage-proof material for well cementation prepad fluid, preparation method of leakage-proof material, well cementation leakage-proof prepad fluid system and application of well cementation leakage-proof prepad fluid system

By preparing nano-scale polymer microspheres in the cementing preliminary fluid and introducing self-crosslinked monomers, the problem of insufficient adaptability of existing cementing leak-proof materials is solved, and the adaptive leak-proof effect is achieved for different formations and cracks, and the protection of the wellbore fluid performance is ensured.

CN119751740AActive Publication Date: 2025-04-04CHINA NAT PETROLEUM CORP +1

Patent Information

Application Number
CN202411746967.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-04-04
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

The existing cementing leakproof materials are insufficient in adaptability to different leakage formations or cracks of different opening degrees, and the impact on the performance of the wellbore working fluid is not fully analyzed.

Method used

A leak-proof material for cementing preliminary liquid is used, which prepares nano-scale polymer microspheres through specific monomer mixing sequence and reverse phase emulsification method, and combines self-crosslinking monomers to form a leak-proof structure with adaptive capabilities.

Benefits of technology

It achieves good adaptability to cracks and gaps of different opening degrees, improves leakage and pressure bearing capacity, and has no significant impact on the performance of the pre-liquid, and has the effect of intelligently identifying the leakage layer and sealing it.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119751740A_ABST
    Figure CN119751740A_ABST
Patent Text Reader

Abstract

The invention provides a leak-proof material for well cementation prepad fluid, a preparation method of the leak-proof material, a well cementation leak-proof prepad fluid system and application of the leak-proof material. The method comprises the following steps: mixing an ester organic monomer, a benzene organic monomer and 2-acrylamido-2-methylpropanesulfonic acid, stirring at 200-300 rpm to obtain a mixed solution, adding water at a speed of 2-10 mL / min, and adjusting the pH value to 6-8 to obtain an emulsion M1; stirring the emulsion M1 at 300-500 rpm, mixing the emulsion M1 with the initiator solution M2, and carrying out a first reaction at 70-75 DEG C to obtain an intermediate product M3; mixing an ester organic monomer and 2-alkenyl amido-2-methylpropanesulfonic acid to obtain a mixture M4; mixing a self-crosslinking monomer, an initiator and water to obtain a mixture M5; the mixture M4 and the mixture M5 are added into the intermediate product M3 at the speed of 2-10 mL / min, a second reaction is conducted, and the leakproof material for the well cementation prepad fluid is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cementing pre-fluid additives, and in particular relates to a leakage-proof material for cementing pre-fluid and a preparation method thereof, and a cementing leakage-proof pre-fluid system and applications thereof. Background Art

[0002] With the advancement of oil and gas exploration and development technology, unconventional resources such as tight oil and gas, shale gas, etc. are becoming a viable option to replace traditional energy. In recent years, the problem of leakage in micro-nano cracks of deep mud shale and shale oil and gas has gradually received attention. Especially in terms of drilling fluid, a variety of leak-proof materials for micro-nano cracks have been formed, mainly based on nano-rigid materials such as micro-nano calcium carbonate and nano zinc oxide whiskers. For example, CN109762541B discloses a micro-nano composite plugging agent for drilling fluid and a preparation method thereof, which contains nano calcium carbonate, nano zinc oxide whiskers, nano emulsified paraffin, flocculants and lubricants, and solid phase particles of different particle sizes keep the cracks open at the cracks, and small solid phase particles and deformed particles construct a spatial structure at the cracks to form an isolation layer with extremely low permeability, which can effectively isolate the wellbore from the formation and prevent the drilling fluid from leaking into the formation.

[0003] Research on drilling fluid leak-proof materials can provide reference for related research in the cementing field, but since the density of cement slurry is often greater than that of drilling fluid, it has higher requirements for the pressure bearing capacity of the formation. Cementing plugging materials have made certain progress in recent years. For example, CN105062440B discloses a plugging and leak-proof material, which is compounded by fibers, polymer microspheres, polymer powders, and blast furnace slag, and uses polymer microspheres and fibers to entangle with each other, and polymer powders to bond polymer microspheres, fibers, and blast furnace slag to improve the pressure bearing capacity of the material. However, the above materials lack strong adaptability in terms of adaptability to different leakage formations or cracks with different openings. In terms of adaptive leak-proof materials, CN115029926A provides a fiber-grafted expandable resin plugging material composition and preparation method and its cementing leak-proof plugging application. The material is obtained by grafting copolymerization of different polymers, and can be deformed and squeezed into the pores formed by the bridging material, effectively plugging 1 to 5 mm cracks under temperature conditions of 20 to 120 ° C. This patent improves the adaptability of leak-proof and plugging materials to cracks of different openings through specific structural design. However, since its mode of action requires "squeezing into" the formation, its adaptability and efficiency still need to be improved, and the impact of the above-mentioned materials on the performance of the wellbore working fluid has not been analyzed and evaluated.

[0004] At present, how to achieve cementing leakage prevention in an efficient and adaptive manner, ensure the pressure-bearing capacity of the leakage-proof layer, and ensure that the leakage-proof and plugging materials have no significant impact on the performance of the cementing fluid, is still a key technical problem that needs to be solved urgently. Summary of the invention

[0005] In order to solve the above problems in the prior art, the purpose of the present invention is to provide a leakproof material for cementing pre-fluid and its preparation method and a cementing leakproof pre-fluid system and its application. The cementing leakproof pre-fluid system of the present invention has stable performance and good adaptability to cracks of different openings and different types of gaps.

[0006] In order to achieve the above object, according to a first aspect of the present invention, a method for preparing a leakage-proof material for cementing pre-fluid is provided, which comprises:

[0007] S1, 2 to 3 parts by mass of an ester organic monomer, 1.5 to 2.5 parts by mass of a benzene organic monomer, and 2 to 2.5 parts by mass of 2-enamide-2-methylpropanesulfonic acid are mixed, and stirred at a stirring speed of 200 to 300 rpm to obtain a mixed solution, water is added to the mixed solution at a speed of 2 to 10 mL / min, and the pH is adjusted to 6 to 8 to obtain an emulsion M1; the emulsion M1 is stirred at a stirring speed of 300 to 500 rpm, and then mixed with an initiator solution M2, and a first reaction is carried out at 70 to 75° C. for 30 to 40 minutes to obtain an intermediate product M3;

[0008] S2, 20-25 parts by mass of ester organic monomers and 0.25-0.5 parts by mass of 2-enamide-2-methylpropanesulfonic acid are mixed to obtain a mixture M4; 2-5 parts by mass of a self-crosslinking monomer, an initiator and water are mixed to obtain a mixture M5; the mixtures M4 and M5 are added to the intermediate product M3 at a feeding rate of 2-10 mL / min, respectively, to carry out a second reaction, and obtain the leak-proof material for cementing pre-fluid.

[0009] In the above-mentioned S1 stage, the present invention uses 2-enamide-2-methylpropanesulfonic acid as an emulsifier and utilizes the reverse emulsification method to realize that the organic monomer mixture forms a nano-scale emulsion in water, thereby ensuring the success rate of preparing the nano-scale microsphere core, improving the dispersion performance of the polymer microsphere, and simplifying the reaction process and materials; utilizing the polymerization activity of 2-enamide-2-methylpropanesulfonic acid and the initiator to promote emulsion polymerization, ensuring the formation of nano-scale solid polymer microspheres. The first reaction temperature in S1 can better take into account the emulsion stability and reaction rate. If the temperature is higher than the above range, it may be detrimental to the stability of the emulsion.

[0010] In the S2 stage, by adding different materials separately and slowly, it is beneficial to ensure the success rate of self-crosslinking monomer polymer, and at the same time ensure that the distribution of self-crosslinking monomer on the surface of microspheres is more random, which is beneficial to improve the crosslinking effect of the microspheres finally formed; the specific monomer mixing order in the present invention can improve the success rate of preparing nano-scale self-crosslinking polymer microspheres.

[0011] The speed of adding water to the mixed liquid is also controlled within the above range, which is conducive to ensuring that the emulsion droplets in the emulsion polymerization have a relatively low particle size, thereby ensuring that the particle size of the polymer microspheres reaches the micro-nano level.

[0012] The preparation method adopts a saponification-free emulsion polymerization method, has a simple raw material composition, and has relatively low process requirements, and can realize industrial production and large-scale promotion and application.

[0013] In some preferred embodiments of the present invention, the ester organic monomer includes methyl methacrylate and / or methyl acrylate; and / or,

[0014] The benzene organic monomer includes divinylbenzene and / or styrene; and / or,

[0015] The initiator comprises persulfate and / or azobisisobutylamidine hydrochloride, preferably, the initiator comprises ammonium persulfate and / or potassium persulfate; and / or,

[0016] The self-crosslinking monomer includes N-methylol acrylamide and / or diacetone acrylamide.

[0017] The above-mentioned ester organic monomers and benzene organic monomers are preferred because they are beneficial to improving the temperature resistance and salt resistance of the polymer microspheres.

[0018] In some preferred embodiments of the present invention, sodium bicarbonate is used to adjust the pH.

[0019] In some preferred embodiments of the present invention, the initiator solution M2 includes 0.05 to 0.07 parts by mass of an initiator and 4 to 8 parts by mass of water.

[0020] In some preferred embodiments of the present invention, 40-60 parts by mass of water are added to the mixed solution to obtain the emulsion M1.

[0021] In some preferred embodiments of the present invention, the mixture M5 includes 0.2 to 0.25 parts by mass of an initiator and 15 to 30 parts by mass of water.

[0022] In some preferred embodiments of the present invention, the temperature of the second reaction is 80-85°C and the time is 2-3 hours. The above second reaction temperature is preferred to be more conducive to obtaining micro-nano-scale polymer microspheres.

[0023] In some preferred embodiments of the present invention, the emulsion M1 is stirred at a stirring speed of 400 to 500 rpm and then mixed with the initiator solution M2.

[0024] In some preferred embodiments of the present invention, in S1, the ester organic monomer is 2 to 2.5 parts by mass, the benzene organic monomer is 1.5 to 2 parts by mass, and the 2-enamide-2-methylpropanesulfonic acid is 2 to 2.3 parts by mass; and / or,

[0025] In S2, the ester organic monomer is 20 to 22 parts by mass, and the 2-enamide-2-methylpropanesulfonic acid is 0.25 to 0.3 parts by mass.

[0026] According to another aspect of the present invention, there is also provided a leakage-proof material for cementing pre-fluid prepared according to the above-mentioned preparation method.

[0027] The leakproof material for cementing pre-fluid of the present invention introduces self-crosslinking monomers on the surface of microspheres through structural design, which can realize self-adaptation to different opening cracks, improve leakproof pressure bearing capacity, and have no significant effect on the performance of pre-fluid. Compared with rigid nanomaterials, micro-nano-scale microspheres are elastic, can enter different types of cracks, and have stronger adaptability; a large number of self-crosslinking monomers are evenly distributed on the surface of the microspheres. After entering the well, when a specific depth is reached, at a specific concentration and temperature, crosslinking can occur between polymer microspheres. Since the contact probability between microspheres in the pre-fluid is low and the contact time is short, the crosslinking behavior is not obvious; when a leaking layer appears, the pre-fluid containing microspheres leaks into the gaps and cracks, and the microspheres gather in large quantities in the gaps and cracks to form a structure with higher pressure bearing capacity, so the self-crosslinking microsphere structure formed by the present invention can enable it to have the effect of intelligently identifying the leaking layer to achieve plugging; at the same time, since the microsphere particles are extremely small, it will basically not have a significant impact on the engineering performance of the pre-fluid.

[0028] According to another aspect of the present invention, a cementing anti-leakage pre-fluid system is also provided, comprising 100 parts by mass of water, 8 to 15 parts by mass of anti-leakage material for cementing pre-fluid, 2 to 5 parts by mass of fiber, 80 to 150 parts by mass of solid phase material, 1.5 to 3 parts by mass of suspension stabilizer, 2 to 3 parts by mass of fluid loss reducer, 4 to 7 parts by mass of anti-pollution agent, and 0.3 to 0.5 parts by mass of anti-foaming agent.

[0029] Preferably, the fiber comprises one or a combination of two or more of lignin fiber, polyvinyl alcohol fiber and polyester fiber; preferably, the fiber has a length of 0.5 to 3 mm and a diameter of 5 to 15 μm.

[0030] Preferably, the solid phase material includes one or a combination of two or more of quartz sand, dolomite powder, barite and microsilicon.

[0031] Preferably, the suspension stabilizer is an AMPS-type medium-temperature pre-liquid suspension stabilizer; preferably, the fluid loss reducer includes an AMPS-type medium-temperature cement slurry fluid loss reducer; preferably, the anti-pollution agent includes an organic phosphonate anti-pollution agent; preferably, the anti-foaming agent includes an organosilicon-type anti-foaming agent.

[0032] In some preferred embodiments of the present invention, when preparing the leakage-proof material for cementing pre-fluid, stirring is performed at a stirring speed of 4000 to 12000 rpm.

[0033] The anti-leakage material for cementing pre-fluid of the present invention is in the form of stable, nano-scale microspheres when the pre-fluid is prepared, and the surface is hydrophilic, so it has good stability and dispersibility in the pre-fluid, does not require additional emulsifiers or dispersants, and has little effect on the rheology and stability of the pre-fluid.

[0034] According to another aspect of the present invention, there is provided an application of the cementing anti-leakage pre-fluid system, which is suitable for plugging cracks with a width of 0.5 mm to 5 mm and different types of pores at 100°C to 180°C.

[0035] In some preferred embodiments of the present invention, the cementing anti-leakage pre-fluid system has a pressure bearing capacity greater than 6.9 MPa and a filtration loss volume less than 40 mL.

[0036] Compared with the prior art, the cementing anti-leakage pre-fluid system of the present invention has the following beneficial effects:

[0037] 1. The cementing anti-leakage pre-fluid system of the present invention is nano-scale, stable solid phase particles, has strong adaptability to different types of pre-fluids, and has good compatibility with pre-fluids;

[0038] 2. The cementing anti-leakage pre-fluid system of the present invention has good adaptability to cracks with different openings and different types of voids, and can adapt to voids and cracks of various shapes and types, playing the role of intelligent leakage prevention;

[0039] 3. The cementing leak-proof pre-liquid leak-proof structure of the present invention has high strength and strong pressure-bearing capacity, and can well achieve the purpose of leak-proofing and reducing filtration loss, and has no adverse effect on the performance of the pre-liquid and cement slurry. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 The particle size distribution diagram in the emulsion M1 of Example 1 is shown.

[0041] Figure 2 The particle size distribution graph in the emulsion M1 of Comparative Example 4 is shown. DETAILED DESCRIPTION

[0042] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.

[0043] Performance test of intelligent polymer anti-leakage material for cementing pre-fluid:

[0044] 1. Particle size evaluation

[0045] The experiment was carried out at room temperature. Before the experiment, the quartz sample pool was washed with ethanol and deionized water in turn; after the sample pool was naturally dried, it was moistened with the liquid to be tested; a pipette was placed close to the bottom of the sample pool, and then the liquid to be tested was slowly squeezed into the sample pool to avoid bubbles; the size and distribution of the nanoemulsion droplets were measured using a Mastersizer 3000 laser particle size analyzer. Each group of experiments was tested 3 times, and the final results were averaged.

[0046] 2. Self-crosslinking

[0047] The self-crosslinking performance was determined by solvent extraction, with the sol content as an indicator. Different samples were dried at different temperatures, and then the dried products were wrapped with filter paper and placed in a Soxhlet extractor. After 24 hours of acetone reflux extraction, they were dried at room temperature to constant weight. The gel content was calculated as the ratio of the final weight to the initial weight.

[0048] Example 1

[0049] This embodiment provides a leak-proof material for cementing pre-fluid and a preparation method thereof, and the specific preparation method includes:

[0050] S1. Weigh 2.5 parts by mass of methyl methacrylate and 2 parts by mass of styrene, add 2.3 parts by mass of 2-enamide-2-methylpropanesulfonic acid, and stir at 200RPM for 3 minutes to form a mixed solution; use a metering pump to add 40 parts by mass of water to the mixed solution at a rate of 2mL / min, and use NaHCO3 to adjust the pH value to 7 to obtain emulsion M1; transfer the mixture M1 to a three-necked flask, then put it into a water bath, stir M1 at 400rpm with a stirrer, and then increase the water bath temperature to 70°C; add 0.06 parts by mass of potassium persulfate to 5 parts by mass of deionized water to prepare an initiator solution M2; add solution M2 to the three-necked flask containing M1, and then react to obtain an intermediate product M3.

[0051] S2. Mix 22.5 parts by mass of methyl methacrylate and 0.3 parts by mass of 2-enamido-2-methylpropanesulfonic acid to obtain a mixture M4; dissolve 3 parts by mass of N-hydroxymethyl acrylamide and 0.23 parts by mass of potassium persulfate in 25 parts by mass of deionized water to obtain a mixture M5; use a metering pump to add solution M4 and solution M5 to a three-necked flask containing M3 at a rate of 2 mL / min, and then heat to 85°C for reaction to obtain a polymer microsphere emulsion, which is a leakage-proof material SSL1 for cementing pre-fluid.

[0052] Example 2

[0053] This embodiment provides a leak-proof material for cementing pre-fluid and a preparation method thereof, and the specific preparation method includes:

[0054] S1. Weigh 2 parts by mass of methyl acrylate and 2.5 parts by mass of divinylbenzene, mix them, add 2.3 parts by mass of 2-enamide-2-methylpropanesulfonic acid, and stir at 200RPM for 3 minutes to form a mixed solution; use a metering pump to add 40 parts by mass of water to the mixed solution at a rate of 2mL / min, use NaHCO3 to adjust the pH value to 7, and prepare emulsion M1; transfer the mixture M1 to a three-necked flask, then put it into a water bath, use a stirrer to stir M1 at 400rpm, and then increase the water bath temperature to 70°C; add 0.05 parts by mass of ammonium persulfate to 5 parts by mass of deionized water to prepare an initiator solution M2; add solution M2 to the three-necked flask containing M1, and then react to obtain an intermediate product M3.

[0055] S2. Mix 20 parts by mass of methyl acrylate and 0.3 parts by mass of 2-enamido-2-methylpropanesulfonic acid to obtain a mixture M4; dissolve 2.2 parts by mass of diacetone acrylamide and 0.23 parts by mass of ammonium persulfate in 25 parts by mass of deionized water to obtain a mixture M5; use a metering pump to add solution M4 and solution M5 to a three-necked flask containing M3 at a rate of 2 mL / min, and then heat to 85°C for reaction to obtain a polymer microsphere emulsion, which is a leak-proof material SSL2 for cementing pre-fluid.

[0056] Example 3

[0057] This embodiment provides a leak-proof material for cementing pre-fluid and a preparation method thereof, and the specific preparation method includes:

[0058] S1. Weigh 2.0 parts by mass of methyl methacrylate and 1.5 parts by mass of styrene, add 2 parts by mass of 2-enamide-2-methylpropanesulfonic acid, and stir at 200RPM for 3 minutes to form a mixed solution; use a metering pump to add 40 parts by mass of water to the mixed solution at a rate of 4mL / min, and use NaHCO3 to adjust the pH value to 7 to obtain emulsion M1; transfer the mixture M1 to a three-necked flask, then put it into a water bath, stir M1 with a stirrer at 500rpm, and then increase the water bath temperature to 75°C; add 0.05 parts by mass of potassium persulfate to 5 parts by mass of deionized water to prepare an initiator solution M2; add solution M2 to the three-necked flask containing M1, and then react to obtain an intermediate product M3.

[0059] S2. Mix 20 parts by mass of diacetone acrylamide and 0.3 parts by mass of 2-enamido-2-methylpropane sulfonic acid to obtain a mixture M4; dissolve 2 parts by mass of N-hydroxymethyl acrylamide and 0.2 parts by mass of potassium persulfate in 25 parts by mass of deionized water to obtain a mixture M5; use a metering pump to add solution M4 and solution M5 to a three-necked flask containing M3 at a rate of 2 mL / min, and then heat to 85°C for reaction to obtain a polymer microsphere emulsion, which is a leak-proof material SSL3 for cementing pre-fluid.

[0060] Implementation 4

[0061] This embodiment provides a leak-proof material for cementing pre-fluid and a preparation method thereof, and the specific preparation method includes:

[0062] S1. Weigh 3.0 parts by mass of methyl methacrylate and 2.5 parts by mass of styrene, add 2.5 parts by mass of 2-enamide-2-methylpropanesulfonic acid, and stir at 200RPM for 3 minutes to form a mixed solution; use a metering pump to add 50 parts by mass of water to the mixed solution at a rate of 6mL / min, and use NaHCO3 to adjust the pH value to 7 to obtain emulsion M1; transfer the mixture M1 to a three-necked flask, then put it into a water bath, stir M1 at 300rpm with a stirrer, and then increase the water bath temperature to 70°C; add 0.07 parts by mass of potassium persulfate to 5 parts by mass of deionized water to prepare an initiator solution M2; add solution M2 to the three-necked flask containing M1, and then react to obtain an intermediate product M3.

[0063] S2. Mix 25 parts by mass of methyl methacrylate and 0.5 parts by mass of 2-enamido-2-methylpropanesulfonic acid to obtain a mixture M4; dissolve 5 parts by mass of N-hydroxymethyl acrylamide and 0.25 parts by mass of potassium persulfate in 25 parts by mass of deionized water to obtain a mixture M5; use a metering pump to add solution M4 and solution M5 to a three-necked flask containing M3 at a rate of 6 mL / min, and then heat to 85°C for reaction to obtain a polymer microsphere emulsion, which is a leakage-proof material SSL4 for cementing pre-fluid.

[0064] Comparative Example 1

[0065] The difference from Example 1 is that 2-enamide-2-methylpropanesulfonic acid is not added in step S1, and the obtained leakproof material is DBL1.

[0066] Comparative Example 2

[0067] The difference from Example 1 is that in step S1, the mixture M1 is transferred to a three-necked flask, which is then placed in a water bath, and M1 is stirred at 200 rpm using a stirrer, and the obtained leakproof material is DBL2.

[0068] Comparative Example 3

[0069] The difference from Example 1 is that in step S1, the mixture M1 is transferred to a three-necked flask, then placed in a water bath, stirred at 400 rpm by a stirrer, and then the water bath temperature is increased to 85° C. The obtained leakproof material is DBL3.

[0070] Comparative Example 4

[0071] The difference from Example 1 is that the preparation steps of the mixture M1 in step S1 are as follows: 2.3 parts by mass of 2-enamide-2-methylpropanesulfonic acid is weighed and dissolved in 40 parts by mass of water in advance; 2.5 parts by mass of methyl methacrylate and 2 parts by mass of styrene are added to the previously prepared 2-enamide-2-methylpropanesulfonic acid aqueous solution, and the pH value is adjusted to 7 with Na2CO3 to obtain emulsion M1. The leakproof material obtained in this comparative example is DBL4.

[0072] Comparative Example 5

[0073] The difference from Example 1 is that in step S2, 22.5 parts by mass of methyl methacrylate are weighed to prepare M4; 0.3 parts by mass of 2-enamido-2-methylpropanesulfonic acid, 3 parts by mass of N-hydroxymethyl acrylamide and 0.23 parts by mass of potassium persulfate are dissolved in 25 parts by mass of deionized water to prepare a mixture M5. The leakproof material obtained in this comparative example is DBL5.

[0074] Comparative Example 6

[0075] The difference from Example 1 is that in step S2, a metering pump is used to directly add solution M4 and solution M5 to the three-necked flask containing M3 at the same time. The leakproof material obtained in this comparative example is DBL6.

[0076] Comparative Example 7

[0077] The difference from Example 1 is that in step S1, 2.5 parts by mass of methyl methacrylate and 2 parts by mass of styrene are weighed and mixed, 2.3 parts by mass of 2-enamide-2-methylpropanesulfonic acid are added, and a mixture is formed by stirring at 100RPM for 3 minutes; 40 parts by mass of water are added to the mixture at a rate of 2mL / min by a metering pump, and the pH value is adjusted to 7 by NaHCO3 to obtain an emulsion M1; the mixture M1 is transferred to a three-necked flask, then placed in a water bath, and M1 is stirred at 100rpm by a stirrer, and then the water bath temperature is increased to 70°C. The leakproof material obtained in this comparative example is DBL7.

[0078] The particle sizes of the leak-proof materials obtained in the above embodiments and comparative examples at room temperature are shown in Table 1.

[0079] Table 1

[0080] Leak-proof material Particle size / nm SSL1 256.24±24.58 SSL2 218.26±34.15 SSL3 204.21±28.36 SSL4 583.25±28.52 DBL1 / DBL2 / DBL3 / DBL4 1050±413.5 DBL5 984±317.5 DBL6 272.56±39.7 DBL7 159.68±20.56

[0081] As can be seen from Table 1, the particle sizes of cementing and leak-proof materials SSL1 to SSL4 are all nanometer-level, indicating that nano-polymer microspheres are formed. Nano-level microspheres can easily adapt to cracks with different openings and different types of pores and have strong adaptability. In Comparative Example 1, 2-enamide-2-methylpropanesulfonic acid was not added, and an emulsion could not be formed to perform emulsion polymerization, so polymer microspheres were not formed, and no data of particle size was displayed; in Comparative Example 2, the stirring speed was lower than the specified speed, and the organic monomer could not be emulsified into smaller emulsion droplets, so polymer microspheres were not formed, and no data of particle size was displayed; in Comparative Example 3, the stirring water bath temperature was higher than the specified temperature, and temperature was a key factor affecting the stability of the emulsion, so the emulsion formed by the organic monomer was unstable, and it was difficult to ensure the emulsion polymerization, and polymer microspheres were not formed, and no data of particle size was displayed; in Comparative Example 4, the specified mixing order was not adopted, so polymer microspheres with nanometer-scale particle size could not be formed, and the product particle size was large and the distribution range was large; in Comparative Example 5, the specified rotation speed was not adopted, and it was difficult to ensure that the emulsion droplets were reduced to nanometer particle size by mechanical energy, and the product particle size was large and the distribution range was large. This is because the synthesis of nanometer polymer microspheres requires that the organic monomers be dispersed into nanometer-scale droplets during emulsion polymerization, which requires a large energy input, one from mechanical energy such as vigorous stirring and ultrasound, and the other from chemical energy. The reverse emulsification method can make full use of the chemical energy of the emulsifier 2-enamido-2-methylpropanesulfonic acid as an emulsifier, thereby forming an emulsion with a smaller particle size, and then preparing nano-scale polymer microspheres. However, it is difficult to directly emulsify the organic monomer into a nano-scale emulsion by directly mixing the organic monomer, water and emulsifier.

[0082] In Example 1 and Comparative Example 4, the particle size distribution of emulsion M1 is as follows: Figure 1 , Figure 2 shown.

[0083] Emulsion droplets were formed in Comparative Examples 6 and 7, so their self-crosslinking properties need to be further investigated.

[0084] Table 2 shows the gel content of different self-crosslinking polymer microspheres after heat treatment at different temperatures. The gel content of the microspheres containing self-crosslinking monomers increased after heat treatment, indicating the existence of self-crosslinking behavior. The cementing and leakproof materials SSL1 to SSL5 all formed a large amount of gel content after heating at 60°C, 120°C, and 140°C. When the temperature reaches 120°C, the polymer can be effectively crosslinked, and the crosslinking can be completely completed at 140°C, which highlights that the prepared microspheres can undergo self-crosslinking under high temperature conditions. Comparative Example 5 also formed a large amount of gel. The gel content of the polymer microspheres formed in Comparative Example 6 after heating at 60°C, 120°C, and 140°C is almost 0. Comparative Example 6 introduces a self-crosslinking monomer in step S2. Although the self-crosslinking monomer is not evenly distributed on the surface of the microsphere, it still exhibits self-crosslinking characteristics; Comparative Example 7 adds the monomer solution too quickly in step 2, and the self-crosslinking monomer fails to be successfully introduced onto the microsphere, so it does not exhibit self-crosslinking characteristics.

[0085] Table 2

[0086]

[0087] Performance evaluation test of cementing intelligent anti-leakage pre-fluid system:

[0088] The HTHP water loss was used to analyze the filtration loss reduction ability of self-crosslinked microspheres. The water loss was measured using a Qiandele high temperature and high pressure water loss instrument, with a test temperature of 140°C, a test pressure difference of 6.9MPa, and a filtration loss time of 30min. In the test, two test media were used, one was the filter paper recommended by API, and the other was a microporous membrane with a pore size of 220nm, which can be used to better simulate microcracks and micropores, and evaluate the leakage prevention ability of self-crosslinked microspheres for such formations. In order to evaluate the temperature response characteristics of the self-crosslinked micro-area, it is necessary to first maintain the cementing fluid containing self-crosslinked microspheres at different temperatures for a period of time to simulate the circulation process of the cementing fluid in the formation, and then take it out and evaluate it using the HTHP water loss instrument.

[0089] Application Example 1

[0090] 10 parts of cementing pre-fluid leakproof material SSL1, 2 parts by mass of suspension stabilizer DRY-S1 (China National Petroleum Corporation Engineering Technology Research Institute Co., Ltd.), 3 parts by mass of fluid loss reducer DRF-2L (China National Petroleum Corporation Engineering Technology Research Institute Co., Ltd.), 5 parts by mass of anti-pollution agent DRP-1L (China National Petroleum Corporation Engineering Technology Research Institute Co., Ltd.), and 0.5 parts by mass of foam inhibitor DRX-1L (China National Petroleum Corporation Engineering Technology Research Institute Co., Ltd.) were dissolved in 100 parts by mass of water and fully stirred; 120 parts of dolomite powder and 3 parts by mass of fibers with a length of 2 to 10 mm were fully mixed, and the solid mixture was slowly poured into the solution while stirring at a speed of 4000 rpm. After the pouring was completed, high-speed stirring was continued to mix evenly to obtain a cementing pre-fluid leakproof system SP1.

[0091] Application Example 2

[0092] 10 parts of cementing pre-fluid leakproof material SSL3, 2 parts by mass of suspension stabilizer DRY-S1 (China National Petroleum Corporation Engineering Technology Research Institute Co., Ltd.), 3 parts by mass of fluid loss reducer DRF-2L (China National Petroleum Corporation Engineering Technology Research Institute Co., Ltd.), 5 parts by mass of anti-pollution agent DRP-1L (China National Petroleum Corporation Engineering Technology Research Institute Co., Ltd.), and 0.5 parts by mass of foam suppressant DRX-1L (China National Petroleum Corporation Engineering Technology Research Institute Co., Ltd.) were dissolved in 100 parts by mass of water and fully stirred; 120 parts of dolomite powder and 3 parts by mass of fibers with a length of 2 to 10 mm were fully mixed, and the solid mixture was slowly poured into the solution under stirring at a speed of 4000 rpm. After the pouring was completed, high-speed stirring was continued to mix evenly to obtain a cementing pre-fluid leakproof system SP2.

[0093] Application Example 3

[0094] 15 parts of cementing pre-fluid leakproof material SSL1, 2 parts by mass of suspension stabilizer DRY-S1 (China National Petroleum Corporation Engineering Technology Research Institute Co., Ltd.), 3 parts by mass of fluid loss reducer DRF-2L (China National Petroleum Corporation Engineering Technology Research Institute Co., Ltd.), 5 parts by mass of anti-pollution agent DRP-1L (China National Petroleum Corporation Engineering Technology Research Institute Co., Ltd.), and 0.5 parts by mass of foam inhibitor DRX-1L (China National Petroleum Corporation Engineering Technology Research Institute Co., Ltd.) were dissolved in 100 parts by mass of water and fully stirred; 120 parts of dolomite powder and 3 parts by mass of fibers with a length of 2 to 10 mm were fully mixed, and the solid mixture was slowly poured into the solution under stirring at a speed of 4000 rpm. After the pouring was completed, high-speed stirring was continued to mix evenly to obtain a cementing pre-fluid leakproof system SP3.

[0095] Application Example 4

[0096] 8 parts of cementing pre-fluid leakproof material SSL1, 2 parts by mass of suspension stabilizer DRY-S1 (China National Petroleum Corporation Engineering Technology Research Institute Co., Ltd.), 3 parts by mass of fluid loss reducer DRF-2L (China National Petroleum Corporation Engineering Technology Research Institute Co., Ltd.), 5 parts by mass of anti-pollution agent DRP-1L (China National Petroleum Corporation Engineering Technology Research Institute Co., Ltd.), and 0.5 parts by mass of foam inhibitor DRX-1L (China National Petroleum Corporation Engineering Technology Research Institute Co., Ltd.) were dissolved in 100 parts by mass of water and fully stirred; 120 parts of dolomite powder and 2 parts by mass of fibers with a length of 2 to 10 mm were fully mixed, and the solid mixture was slowly poured into the solution while stirring at a speed of 4000 rpm. After the pouring was completed, high-speed stirring was continued to mix evenly to obtain a cementing pre-fluid leakproof system SP4.

[0097] Application Comparative Example 1

[0098] The cementing pre-fluid SPD1 was prepared according to the method of Application Example 1, except that no leak-proof material for cementing pre-fluid was used.

[0099] Application Comparative Example 2

[0100] The cementing anti-leakage pre-pad fluid SPD2 was prepared according to the method of Application Example 1, except that no fiber was used.

[0101] Application Comparative Example 3

[0102] The cementing pre-fluid SPD3 was prepared according to the method of Application Example 1, except that the amount of the cementing pre-fluid leakage-proof material SSL1 added was 5 parts by weight.

[0103] Application Comparative Example 4

[0104] The cementing pre-fluid SPD4 was prepared according to the method of Application Example 1, except that the leak-proof material DBL4 prepared in Comparative Example 4 was used instead of the leak-proof material SSL1 for cementing pre-fluid.

[0105] Application Comparative Example 5

[0106] The cementing pre-fluid SPD5 was prepared according to the method of Application Example 1, except that the leak-proof material DBL5 prepared in Comparative Example 5 was used instead of the leak-proof material SSL1 for cementing pre-fluid.

[0107] The leak-proofing and plugging performance of the cementing anti-leakage prefluid on different simulated media was tested at 60°C, 120°C and 140°C, respectively. The results are shown in Tables 3, 4, 5 and 6.

[0108] Table 3

[0109]

[0110] Table 4

[0111]

[0112] Table 5

[0113]

[0114] Table 6

[0115]

[0116] It can be seen from Table 4 that at a temperature of 60°C, the self-crosslinked microspheres did not play their role in preventing leakage. This is because the self-crosslinking temperature was not reached, and no crosslinking structure was formed between the microspheres, and the pressure bearing capacity was difficult to meet 6.9 MPa. It can be seen from Table 5 that at 120°C, the application examples all showed good leakage prevention effects, with a pressure bearing capacity of >6.9 MPa, and a cumulative leakage of less than 40 mL. In the application of comparative example 1, no leak-proof material for cementing pre-fluid was added, and the pre-fluid could not play the role of leak-proof and plugging at all, and gas penetration occurred; in the application of comparative example 2, no fiber material was added, and it could not play a bridging role, so the leakage was large; in the application of comparative example 3, the amount of leak-proof material for cementing pre-fluid was less than the prescribed amount, so the leakage was large; the particle size of the microspheres of the leak-proof material for cementing pre-fluid used in comparative example 4 was large, and it was difficult to achieve intelligent adaptation to cracks, and it was impossible to form a dense leak-proof plugging structure, so the leak-proof and plugging ability was poor; in the application of comparative example 5, the self-crosslinking monomer on the surface of the microspheres used was unevenly distributed, resulting in premature crosslinking of the self-crosslinking microspheres during the high-temperature cycle, so the leak-proof ability decreased. It can be seen from Table 5 that after reaching the self-crosslinking temperature, the microspheres can have a good leak-proof effect in a large temperature range. It can be seen from Table 6 that the viscosity of application example 1 changes little under 140°C curing, while the apparent viscosity of comparative example 5 increases significantly, which also shows that the self-crosslinking microspheres in comparative example 5 undergo crosslinking, increasing the viscosity of the system.

[0117] It can be seen from Table 5 that after reaching the self-crosslinking temperature, the microspheres can have a good leak-proof effect within a larger temperature range.

[0118] It can be seen from Table 6 that the viscosity of Example 1 changes little under curing at 140°C, while the apparent viscosity of Comparative Example 5 increases significantly, which also indicates that the self-crosslinking microspheres in Comparative Example 5 undergo crosslinking, increasing the viscosity of the system.

[0119] Evaluation on compatibility between cementing anti-leakage pre-fluid system and cement slurry:

[0120] According to the national standard GB / T19139-2012 "Test Methods for Oil Well Cement", the influence of leakage-proof materials used in cementing pre-pad fluid on the rheological properties of the pre-pad fluid was tested. The results are shown in Table 7.

[0121] Table 7

[0122] Leak-proof pre-fill fluid Rheology SPD1 7 / 10 / 27 / 35 / 41 / 56 SP1 8 / 10 / 27 / 35 / 43 / 61 SP3 8 / 10 / 27 / 36 / 44 / 62

[0123] SPD1 does not add the anti-leakage material microspheres for cementing pre-fluid, the amount of microspheres added in SP1 is 10 parts by mass, and the amount of microspheres added in SP3 is 15 parts by mass. It can be seen that after adding the anti-leakage material microspheres for cementing pre-fluid to the pre-fluid, as the amount of microspheres added increases, the apparent viscosity of the pre-fluid at room temperature increases slightly, meeting the construction requirements. This is mainly because the microspheres do not form polymer colloids with a large hydrodynamic radius in water, and have little restraint on free water, so they do not produce a significant viscosity-increasing effect.

[0124] In summary, the leak-proof material for cementing prefluid of the present invention has strong adaptability, can seal different types of micro-nano-level cracks and pores, has a pressure resistance of more than 6.9 MPa, and a filtration loss of less than 40 mL, thereby achieving the purpose of leak-proofing and reducing filtration loss, and has no adverse effect on the performance of the prefluid and cement slurry, meeting the leak-proofing requirements for cementing in shale layers with developed microcracks and pores.

Claims

1. A method for preparing a leak-proof material for cementing pre-fluid, characterized in that: include: S1, 2 to 3 parts by mass of an ester organic monomer, 1.5 to 2.5 parts by mass of a benzene organic monomer, and 2 to 2.5 parts by mass of 2-enamide-2-methylpropanesulfonic acid are mixed, and stirred at a stirring speed of 200 to 300 rpm to obtain a mixed solution, water is added to the mixed solution at a speed of 2 to 10 mL / min, and the pH is adjusted to 6 to 8 to obtain an emulsion M1; the emulsion M1 is stirred at a stirring speed of 300 to 500 rpm, and then mixed with an initiator solution M2, and a first reaction is carried out at 70 to 75° C. for 30 to 40 minutes to obtain an intermediate product M3; S2, 20-25 parts by mass of ester organic monomers and 0.25-0.5 parts by mass of 2-enamide-2-methylpropanesulfonic acid are mixed to obtain a mixture M4; 2-5 parts by mass of a self-crosslinking monomer, an initiator and water are mixed to obtain a mixture M5; the mixtures M4 and M5 are added to the intermediate product M3 at a feeding rate of 2-10 mL / min, respectively, to carry out a second reaction, and obtain the leak-proof material for cementing pre-fluid.

2. The preparation method according to claim 1, characterized in that: The ester organic monomer includes methyl methacrylate and / or methyl acrylate; and / or, The benzene organic monomer includes divinylbenzene and / or styrene.

3. The preparation method according to claim 1, characterized in that: The self-crosslinking monomer includes N-methylol acrylamide and / or diacetone acrylamide.

4. The preparation method according to claim 1, characterized in that: The initiator solution M2 includes 0.05 to 0.07 parts by mass of an initiator and 4 to 8 parts by mass of water.

5. The preparation method according to claim 1, characterized in that: 40-60 parts by mass of water are added to the mixed solution to obtain the emulsion M1.

6. The preparation method according to claim 1, characterized in that: The mixture M5 includes 0.2 to 0.25 parts by mass of an initiator and 15 to 30 parts by mass of water.

7. The preparation method according to claim 1, characterized in that: The temperature of the second reaction is 80-85° C. and the time is 2-3 hours.

8. The preparation method according to claim 1, characterized in that: The initiator includes persulfate and / or azobisisobutylamidine hydrochloride.

9. The preparation method according to claim 1, characterized in that: The emulsion M1 is stirred at a stirring speed of 400 to 500 rpm and then mixed with the initiator solution M2.

10. The preparation method according to claim 1, characterized in that: In S1, the ester organic monomer is 2 to 2.5 parts by mass, the benzene organic monomer is 1.5 to 2 parts by mass, and the 2-enamide-2-methylpropanesulfonic acid is 2 to 2.3 parts by mass; and / or, In S2, the ester organic monomer is 20 to 22 parts by mass, and the 2-enamide-2-methylpropanesulfonic acid is 0.25 to 0.3 parts by mass.

11. A leak-proof material for cementing pre-fluid prepared by the preparation method according to any one of claims 1 to 10.

12. A cementing anti-leakage pre-fluid system, characterized in that: The invention comprises 100 parts by weight of water, 8 to 15 parts by weight of the anti-leakage material for cementing pre-fluid according to claim 11, 2 to 5 parts by weight of fiber, 80 to 150 parts by weight of solid phase material, 1.5 to 3 parts by weight of suspension stabilizer, 2 to 3 parts by weight of fluid loss reducer, 4 to 7 parts by weight of anti-pollution agent, and 0.3 to 0.5 parts by weight of anti-foaming agent.

13. An application of the cementing anti-leakage pre-fluid system according to claim 12 in plugging cracks and pores, characterized in that: The applicable temperature is 100-180°C and the crack width is 0.5-5mm.

Citation Information

Patent Citations

  • Nano composite plugging agent and preparation method and application thereof

    CN110684152A

  • Preparation method of environment-friendly high-temperature-resistant water-based drilling fluid plugging anti-collapse agent

    CN111138594A

  • Synthesis of nano-emulsion blocking agent and water-based drilling fluid

    CN113403047A

  • Salt-tolerant self-adaptive plugging agent capable of resisting high temperature of 230 DEG C and preparation method thereof

    CN114874375A

  • Crosslinking monomer and polymer microsphere blocking material as well as preparation method and application thereof

    CN115701421A

Cited By

  • Leak-proof material for well cementation pad fluid and preparation method therefor, and well cementation leak-proof pad fluid system and use thereof

    WO2026113648A1